REPRESENTASI PEREMPUAN DALAM FILM SATRIA DEWA GATOTKACA (ANALISIS SEMIOTIKA) - Cendiberdi, Reza; Priyadi, Antonius Totok; Seli, Sesillia (Universitas Tanjungpura, 2024)
This study aims to examine the representation of women in the film